A class of rearrangement optimization problems involving the p-Laplacian. (January 2015) - Qiu, Chong; Huang, Yisheng; Zhou, Yuying
Abstract: We investigate two optimization problems related to a quasilinear boundary value problem involving the p -Laplace operator. These optimization problems are formulated relative to the rearrangement of a fixed function. Under some suitable assumptions, we show that both problems are solvable.